2013
DOI: 10.1093/ejcts/ezs676
|View full text |Cite
|
Sign up to set email alerts
|

Management of moderate secondary mitral regurgitation at the time of aortic valve surgery†

Abstract: Secondary MR improves after AVR even without mitral surgery. Concomitant mitral surgery was significantly associated with greater improvement of postoperative MR, but had no significant impact on survival. However, patients who did not improve immediately after AVR had compromised survival. Patients in AF should have mitral valve repair at the time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
4
33
0
2
Order By: Relevance
“…This can be explained by the progressive reduction of the incidence of rheumatic mitral disease in western countries and by the high incidence of functional MR in that context (up to 75%). In a previous work, 8 we have shown that when we choose to intervene on secondary MR at the time of aortic valve replacement, the repair rate can be greater than 95% in this subset of patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This can be explained by the progressive reduction of the incidence of rheumatic mitral disease in western countries and by the high incidence of functional MR in that context (up to 75%). In a previous work, 8 we have shown that when we choose to intervene on secondary MR at the time of aortic valve replacement, the repair rate can be greater than 95% in this subset of patients.…”
Section: Discussionmentioning
confidence: 86%
“…7 The growing sense of the negative impact on clinical outcomes of secondary moderate mitral regurgitation (MR) at the time of AVS renewed the interest of intervening earlier on this valve. 8 Furthermore, because most of the time the mitral valve is structurally normal, it seems logical to repair rather than to replace it. Most of the published articles on this field involve rheumatic mitral disease, which can give a false overview of the current problem that surgeons are faced with in daily practice.…”
Section: Supplemental Materials Is Available Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…However, most sizeable studies had a mixed patient with AS/AR population, and the patients with AR always account for only a small part. Ruel et al evaluated secondary MR in 848 patients with AVR, only 31 of which had severe AR concomitant with 2+ MR. Coutinho et al reported a series of 255 patients with AVR who had secondary 2+ MR, among whom 76 had AR. In another large institutional report from the Mayo Clinic, Wan et al identified 190 ≥2+ secondary patients with MR, among whom only 25 had AR.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013 Coutinho et al 23 compared mortality in two groups of patients with severe as and associated hemodynamically significant MR : one underwent AVR alone, the other underwent combined mitral and aortic valve surgery. this study failed to demonstrate a significant better survival in patients undergoing combined surgery; however, patients with persistent Mr at discharge had significantly higher mortality compared to patients without persistent Mr, underscoring the role of persistent MR on mortality after AVR.Lack of difference in survival between patients with isolated and combined valve surgery can be explained with the high rate of Mr improvement in patients undergoing aVr alone (67.4%).…”
Section: Impact Of Significant Mr On Mortality In Patients Undergoingmentioning
confidence: 99%